The New Norm UMP Staffs 3 Working Procedures during CMCO - Siti Nur Azwin, Zulkapri (2020)
Pekan, 27 May 2020 – Universiti Malaysia Pahang (UMP) campus recovers its’ former liveliness after almost two months being left due to the Restriction Movement Order (RMO) in the fight against the COVID-19 pandemic.